A literature review of information technology governance implementation in higher educations - Liew, Chinwei; Aziati, A. H. Nor; Abdullah, Nor Hazana (American Scientific Publishers, 2018)
Past researches of Information Technology Governance (ITG) had been heavily focused on profit-oriented organizations that are rooted in highly competitive and dynamic markets. Researches on ITG of higher education had been considerably lacking in comparison. This paper attempts to analyze issues faced by several high institutions and universities in the process of ITG implementation. Data was mainly collected from case studies of universities in ITG implementation as case studies present significant empirical evidence for further analysis. The results revealed that issue in ITG structure had been the main barrier to effective ITG implementation in universities. Universities were also troubled with strategic alignment and intercommunications among units within the organizations. Apart from issues above, results further revealed that universities of Malaysia had been lacking in ITG awareness, and supports from board of managements in ITG implementation. This paper concludes by presenting possible practices to be taken in order to counteract the issues faced by universities in ITG implementation.